Implementation of the Merdeka Curriculum in MAN Gunungsitoli City - Dawolo, Surya Rahmani; Arsyad, Junaidi; Budianti, Yusnaili (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to describe the implementation of the Independent Curriculum at MAN Gunungsitoli City, including the challenges faced and the efforts made to overcome them. The Independent Curriculum is an educational innovation that emphasizes project-based learning, differentiation, and strengthening the Pancasila Student Profile. This study uses a descriptive qualitative method with a case study approach. Data collection was carried out through observation, interviews, and documentation involving the principal, vice principal for curriculum, teachers, and students. The results of the study indicate that the implementation of the Independent Curriculum at MAN Gunungsitoli City has gone quite well, although there are still some challenges. The most prominent achievement is the implementation of differentiated learning and project-based activities that strengthen the Pancasila Student Profile, which has increased student engagement and creativity. In addition, teachers have begun to integrate local wisdom values ​​into project-based learning. The unequal understanding of the core principles of the Independent Curriculum is also a significant challenge. Efforts to overcome these problems are by conducting collaborative internal training, forming teacher learning communities, and strengthening curriculum management at the school level. The consistency of the principal’s involvement in providing supervision and motivation is also a major supporting factor in curriculum implementation. The results of the study concluded that, although the implementation of the Merdeka Curriculum has not been fully optimal, MAN Gunungsitoli City has shown a strong commitment to adapting to this new learning paradigm. Recommendations are addressed to the school and the Ministry of Religion to strengthen support in terms of facilities, teacher training, and regular monitoring and evaluation in order to achieve more holistic and contextual educational goals.